Concept of Prefetching and Caching in Web Usage Mining - Chauhan, Pushpraj Singh; Dixit, Sarvottam; Jain, Suresh (International Journal of Computer Sciences and Engineering, 2018)
Since the growth of internet is increasing day by day, hence the amount of data that is storing in Web Server is also increasing rapidly. The growth of number of users of internet is also increasing at a rapid rate, this in turn increasing the Web traffic, so we need some type of strategies or mechanism that can handle this rapid growth of Web traffic. Web Prefetching and caching are techniques that can be used to deal with this increased growth of Web Traffic. Web prefetching and caching are processes that prefetch frequent pages which are likely to be requested in near future and caching is used to store these pages in Proxy Cache Server. Here we have proposed some cache replacement policies by which the hit ratio is likely to get increased. We have proposed novel pre fetching and caching scheme to access frequent data items. It helps in improving pattern analysis, and pattern generation process. Proposed techniques will be useful in E-commerce, Web personalization for customer requirement & satisfaction. This will reduce the user overall access time in future.